THE UTILIZATION OF LINE VIDEO CALL AND TIKTOK VIDEO FOR TEACHING PRONUNCIATION IN THAILAND - Lilis Kartika Dewi; Yudhi Arifani (University of Muhammadiyah Malang, 2021)
This study attempts to explore the utilization of LINE video call for teaching pronunciation using the TikTok video, seen from teacher and students' perspectives. This qualitative study involves a teacher and three students in Thailand interviewed through an online platform. The findings showed that both teacher and students gained a positive attitude towards utilizing LINE video call for teaching pronunciation using TikTok. The benefits are increasing students' vocabulary, building self-confidence in pronouncing the words in English, and more interest in joining the class since the application is not boring. On the other hand, the teacher has a problem with the limited time in creating the materials and making the students focus on the learning process. Yet, the students have a problem with internet connection and many assignments to do during online learning. Finally, the students are enthusiastic since TikTok and LINE video calls help them learn English, especially their pronunciation.